Beaconsfield chronic epoch - Garlake, Margaret 1939- (Black Dog Publishing, 2015)
The first major book on Beaconsfields history, this exciting publication is both the record of an artists organisation, and that of an expansive curatorial journey within the art world taken by two artists trained as painters. From the first organisational forays within the creative partnership of David Crawforth and Naomi Sederfin culminating in the Nosepaint event of May 1991, this book then follows their journey from Nosepaint to the formal opening of Beaconsfield in September 1995 to the present, profiling how each project and initiative was approached with the same ethic and ethos throughout a collective Chronic Epoch. The importance of the books story is as much an important record as it is an inspiration to any burgeoning creator. To look at the self-created etymology behind the name says as much; Beaconsfield: to offer a space for artists and audiences to experience high quality (hence beacon), challenging, new artworks in a wide range (hence field) of contemporary visual art media through commissions, group exhibitions, performances, publications and events. Published in partnership with the organisation, in heavily visual sections and with contributions from those such as BobandRobertaSmith, Gustav Metzger, Paul Hobson and Julian Stallabrass, this book relays the story of a space constructed with a desire to fill a niche between the institution, the commercial and the alternative and indeed how it has sustained its own ethical and artistic standards throughout and fostered a fresh take on modern art in the process
Includes bibliographical references
Keywords: Beaconsfield -- London; Geschichte 1900-2000; Geschichte 1994-2014; Art, Modern / 20th century; Art, Modern / 21st century; Art / England / Beaconsfield; Kunst; Projekt; Aufsatzsammlung